Stringent Selection of Knobby Plasmodium falciparum-Infected Erythrocytes during Cytoadhesion at Febrile Temperature - Dörpinghaus, Michael (Microorganisms, 2020)
Changes in the erythrocyte membrane induced by Plasmodium falciparum invasion allow cytoadhesion of infected erythrocytes (IEs) to the host endothelium, which can lead to severe complications. Binding to endothelial cell receptors (ECRs) is mainly mediated by members of the P. falciparum erythrocyte membrane protein 1 (PfEMP1) family, encoded by var genes. Malaria infection causes several common symptoms, with fever being the most apparent. In this study, the effects of febrile conditions on cytoadhesion of predominately knobless erythrocytes infected with the laboratory isolate IT4 to chondroitin-4-sulfate A (CSA), intercellular adhesion molecule 1 (ICAM-1), and CD36 were investigated. IEs enriched for binding to CSA at 40 °C exhibited significantly increased binding capacity relative to parasites enriched at 37 °C. This interaction was due to increased var2csa expression and trafficking of the corresponding PfEMP1 to the IE surface as well as to a selection of knobby IEs. Furthermore, the enrichment of IEs to ICAM-1 at 40 °C also led to selection of knobby IEs over knobless IEs, whereas enrichment on CD36 did not lead to a selection. In summary, these findings demonstrate that knobs are crucial for parasitic survival in the host, especially during fever episodes, and thus, that selection pressure on the formation of knobs could be controlled by the host.